Optimal control algorithm design for a prototype of active noise control system - Manzano Ramos, Edgar André (2017)
This little work was made with help of: Mother, all of this is because of you. My family in Puno, thanks for your love and support. My family in Lima, especially Mrs. Dora and my Aunt Jacqui, thanks for all. PUCP and Concytec, thanks for the opportunity. Mr. Calderon, thank you for all your academic advise.